Effect of Silane Treatments and Fiber Loadings on Tensile Properties of Coir Fiber Reinforced Composites - Al Emran Ismail; Mohd Hisham Sa'at (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my